A case of severe acute exacerbation of Yokkaichi asthma treated with a vibrating mesh nebulizer. (2016) - Yano, Takeshi; Yonaha, Tetsu; Hidaka, Koutaro; Nagahama, Masumi; Koshida, Tomohiro; Matsuoka, Hiroshi; Taniguchi, Masahiko; Tsuneyoshi, Isao
Abstract: Yokkaichi asthma was one of the most common environmental pollution diseases in Japan in the 1960s and 1970s. The problem of air pollution in Yokkaichi was solved in the 1970s. However, mortality and life expectancy were still affected by the late effects of air pollution in patients with Yokkaichi asthma even in the 2000s. In this case report, we described the experience of successful treatment of a patient with severe asthmatic status due to Yokkaichi asthma. A 40s-year-old man, who was officially certified as a patient with Yokkaichi asthma from his infancy, was admitted to hospital due to acute exacerbation of asthma. Mechanical ventilation, intravenous administration of aminophylline and dexamethasone, enteral administration of montelukast, and a transdermal patch of tulobuterol were started. However, because of the lack of improvement in clinical status, inhalation of procaterol using vibrating mesh nebulizer systems was started. Inhalation of procaterol was used three times a day. After using the vibrating mesh nebulizer, respiratory system compliance and hypercapnia rapidly improved. Bilateral expiratory wheezing was diminished. Weaning from mechanical ventilation was initiated, and on the eighth day of mechanical ventilation, the patient was extubated. Although intractable respiratory failure with decreased respiratory system compliance resulting from the late effects of air pollution and a long-time asthmatic inflammatory condition was observed, the use of a vibrating mesh nebulizer for the inhaled administration of procaterol was useful to relieve severe bronchospasm due to Yokkaichi asthma.